Decision Support System Pemilihan Jurusan Berdasarkan Minat Siswa Pada SMK Negeri 5 Palu - Mohammad Renaldy; Fitriyanti Andi Masse; Ika Fatmawati (Jurnal Elektronik Sistem Informasi dan Komputer, 2025)
The majors will be adjusted to the student's academic abilities and interests. The purpose of this major is so that students can be directed in receiving lessons that are in accordance with the abilities and talents possessed by students. This department is held to select and collect the same ability of students to take the same educational program as well. In the Decision Support System, the selection of majors is based on students' interests in SMK Negeri 5 Palu. The criteria to be used are: the value of Indonesian Language, English, Science and Mathematics subjects.  The purpose of this research is to make it easier for SMK Negeri 5 Palu to determine students who are accepted into each department based on the results of recommendations from the decision support system. The method used is Weighted product. The research conducted in this case is Qualitative research. The types of data used in this study are divided into 2 (two), namely primary data and secondary data. Data collection techniques include: observation, interviews and literature. The development of the system uses prototypes. The programming language used is PHP, the database uses MySQL and the editor uses sublime text. The results of the study are a decision support system that applies calculations with the Weighted Product method can produce recommendations for choosing majors to prospective new students of SMK Negeri 5 Palu so that schools can use predetermined criteria to determine who is entitled to enter the chosen major. The processing of questionnaire data obtained a percentage of 24.20% from respondents, the low percentage obtained was due to the lack of information known to new students about the existence of a Supporting Information System for Major Election Decisions at SMK Negeri 5 Palu.